Highly cytotoxic, cyclometalated iridium(iii)-5-fluoro-8-quinolinol complexes as cancer cell mitochondriotropic agents. (4th May 2020) - Qin, Li-Qin; Zou, Bi-Qun; Qin, Qi-Pin; Wang, Zhen-Feng; Yang, Lin; Tan, Ming-Xiong; Liang, Chun-Jie; Liang, Hong
Abstract : Ir-3 and Ir-4 kill HeLa cells and trigger caspase-mediated mitochondrial dysfunction apoptosis pathways. Abstract : Four mononuclear cyclometalated iridium(iii ) complexes, namely, [Ir(FQ)(L1)2 ] (Ir-1 ), [Ir(FQ)(L2)2 ] (Ir-2 ), [Ir(FQ)(L3)2 ] (Ir-3 ) and [Ir(FQ)(L4)2 ]·2CH3 OH (Ir-4 ) using 5-fluoro-8-quinolinol (H-FQ)-based ligands and [(C^N)2 IrCl(μ-Cl)]2 precursor have been first synthesised. The two most effective complexes (containing 7, 8-benzoquinoline (H-L3 ) and 1-phenylpyrazole (H-L4 )), Ir-3 and Ir-4, kill HeLa cells in the nanomole range, with the IC50 values of 0.170 ± 0.05 and 0.035 ± 0.002 μM, respectively, indicating that they could potentially inhibit HeLa tumour populations at a lower concentration. Encouragingly, Ir-3 and Ir-4 induce HeLa apoptosis, as indicated by the clear changes in the apoptosis-associated proteins; both accumulate to a high extent in the mitochondrial fraction; promote mitochondrial membrane (MMP) depolarisation and loss of MMP; and trigger caspase-mediated mitochondrial dysfunction apoptosis pathways. To the best of our knowledge, this study is the first to synthesize cyclometalated iridium(iii )-5-fluoro-8-quinolinol complexes that can function as mitochondrion-targeting anticancer drugs.